EFFECT OF KEVLAR FIBERS ON THE MECHANICAL BEHAVIOR FOR SOME OF EPOXY CHOPPED CARBON FIBER COMPOSITES - Sadeq, Noor (Iraqi Journal of Science, 2024)
This research has been done by reinforcing the matrix (epoxy) resin with two kinds of the reinforcement.One volume fractions was used (30%), Epoxy reinforced with chopped carbon fiber with and second reinforcement was epoxy reinforced with hybrid reinforcements which was the three laminates Kevlar fiber and chopped carbon fibers. After preparation of composite materials some of the mechanical properties have been studied of samples preparation. They were Tensile strength test, flexural strength test, Impact test, and Brinell hardness testThe studied show the tensile strength, flexural strength, shear stress and impact strength of the hybried composites values were increased with existence of Kevlar fibers, while the hardness was decrease. But the reinforcement with carbon fibers increases the hardness and decreases other tests.